1997
DOI: 10.1074/jbc.272.16.10558
|View full text |Cite
|
Sign up to set email alerts
|

The Reversible Antiport-Uniport Conversion of the Phosphate Carrier from Yeast Mitochondria Depends on the Presence of a Single Cysteine

Abstract: Wild type and mutant phosphate carriers (PIC) fromSaccharomyces cerevisiae mitochondria were expressed in Escherichia coli as inclusion bodies, solubilized, purified, and optimally reconstituted into liposomal membranes. This PIC can function as coupled antiport (P i ؊ / P i ؊ antiport and P i ؊ net transport, i.e. P i ؊ /OH ؊ antiport) and uncoupled uniport (mercuric chloride-induced P i ؊ efflux). The basic kinetic properties of these three transport modes were analyzed. The kinetic properties closely resemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 44 publications
(71 reference statements)
4
53
0
1
Order By: Relevance
“…The study of mitochondrial anion carriers has shown that limited modifications can convert carriers into channels. These modifications include manipulation of the ionic composition of the medium in the case of the ADP\ATP carrier [91], chemical modification in the case of the phosphate carrier [92], or site-directed mutagenesis in the case of UCP1 [93]. Following such modifications, a loss of specificity of the transport was noted, and sometimes the channel exhibited certain pore-like properties and allowed large molecules to go through.…”
Section: Uncoupling Mechanism Of Ucp1mentioning
confidence: 99%
“…The study of mitochondrial anion carriers has shown that limited modifications can convert carriers into channels. These modifications include manipulation of the ionic composition of the medium in the case of the ADP\ATP carrier [91], chemical modification in the case of the phosphate carrier [92], or site-directed mutagenesis in the case of UCP1 [93]. Following such modifications, a loss of specificity of the transport was noted, and sometimes the channel exhibited certain pore-like properties and allowed large molecules to go through.…”
Section: Uncoupling Mechanism Of Ucp1mentioning
confidence: 99%
“…In forward exchange kinetic measurements, the initial transport rate was calculated from the radioactivity taken up by the proteoliposomes after 1 min in the initial linear range of substrate uptake. In backward exchange experiments, the decrease in radioactivity inside the liposomes was fitted to the equation: ␣ ϭ 100 (1 Ϫ e Ϫkt ), where ␣ is the percentage of isotopic equilibrium (20). The rates were expressed as apparent velocities, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Inorganic phosphate, which is vital for oxidative phosphorylation, is transported to the mitochondrial matrix by two partly redundant carriers, Mir1 and Pic2 (22,23). Interestingly, Mir1 is also involved in protein import into mitochondria (24), and Pic2 can reversibly change its transport mode (antiport-uniport) according to the redox conditions (25). More generally, phosphate is involved in the homeostasis of several cations in different cellular compartments (26).…”
mentioning
confidence: 99%